Post-Treatment with Erinacine A, a Derived Diterpenoid of H. erinaceus, Attenuates Neurotoxicity in MPTP Model of Parkinson's Disease - Kam-Fai Lee; Shui-Yi Tung; Chih-Chuan Teng; Chien-Heng Shen; Meng Chiao Hsieh; Cheng-Yi Huang; Ko-Chao Lee; Li-Ya Lee; Wan-Ping Chen; Chin-Chu Chen; Wen-Shih Huang; Hsing-Chun Kuo (MDPI AG, 2020)
Hericium erinaceus, a valuable pharmaceutical and edible mushroom, contains potent bioactive compounds such as H. erinaceus mycelium (HEM) and its derived ethanol extraction of erinacine A, which have been found to regulate physiological functions in our previous study. However, HEM or erinacine A with post-treatment regimens also shows effects on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity, but its mechanisms remain unknown. By using annexin-V−fluorescein-isothiocyanate (FITC)/propidium iodide staining and a 2’,7’ −dichlorofluorescin diacetate (DCFDA) staining assay, the cell death, cell viability, and reactive oxygen species (ROS) of 1-methyl-4-phenylpyridinium (MMP+)-treated Neuro-2a (N2a) cells with or without erinacine A addition were measured, respectively. Furthermore, signaling molecules for regulating the p21/GADD45 cell death pathways and PAKalpha, p21 (RAC1) activated kinase 1 (PAK1) survival pathways were also detected in the cells treated with MPP+ and erinacine A by Western blots. In neurotoxic animal models of MPTP induction, the effects of HEM or erinacine A and its mechanism in vivo were determined by measuring the TH-positive cell numbers and the protein level of the substantia nigra through a brain histological examination. Our results demonstrated that post-treatment with erinacine A was capable of preventing the cytotoxicity of neuronal cells and the production of ROS in vitro and in vivo through the neuroprotective mechanism for erinacine A to rescue the neurotoxicity through the disruption of the IRE1α/TRAF2 interaction and the reduction of p21 and GADD45 expression. In addition, erinacine A treatment activated the conserved signaling pathways for neuronal survival via the phosphorylation of PAK1, AKT, LIM domain kinase 2 (LIMK2), extracellular signal-regulated kinases (ERK), and Cofilin. Similar changes in the signal molecules also were found in the substantia nigra of the MPTP, which caused TH+ neuron damage after being treated with erinacine A in the post-treatment regimens in a dose-dependent manner. Taken together, our data indicated a novel mechanism for post-treatment with erinacine A to protect from neurotoxicity through regulating neuronal survival and cell death pathways.